National Commission For Integrated Water Resources Development Plan Report Of Working Group On Prioritisation Of Ongoing & New Projects - Planning Commission (Planning Commission, 1999)
India is an agrarian country with the majority of the population dependant on agriculture. Irrigation through different schemes had been implemented during Pre-plan period. Over the plan period thousands of major, medium, minor schemes were taken up and this has greatly assisted the green revolution in the country. However for various reasons the number of schemes under construction increased considerably during V Plan, AP 78-80, and VI Plan. Also cost and time over runs’ became a serious problem. This situation along with the general decline in the priority of water sector has lead to thin spreading of limited resources. Apart from the limitation of funding there are a number of other constraints like delay in land acquisition, forest clearance, environmental aspect, resettlement and rehabilitation.
Ministry of Water Resources
Ministry of Water Resources